THE BIO-PRESERVATION OF BUFFALO MEAT MANUFACTURED (PASTRAMA) BY USING LACTOBACILLUS PLANTARUM BACTERIA - & Alalaq, Alrubeii (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Bacterial starter Lactobacillus plantarum at concentration of 5% was added to the pastarma which was manufactured by using buffalo meat at ratio of 3 meat: 1fat. The fermentation process was done at 37 Co and relative humidity of 80-85% for 48 hours for each inoculated sample. After this process, spices and garlic were added, the pastrama was stuffed in natural covers. The pastrama was matured at 15-17 Co and relative humidity degree of 75-80% for 3 weeks. This study was carried out for following effect of the bio preservation by using Lactobacillus plantarum in the buffalo meat pastarma the microbial tests of the meat mixture showed that the total count of microorganisms, coliform bacteria, molds and yeasts count, the Staphylococci aureus, and the lactic acid bacteria count were 64×104, 68×102, 41×102, 27×102 and 62×102 CFU/ g respectively. The moisture, protein . fat and ash %, pH, free fatty acids ratio, cholesterol concentration, peroxide value and Thiobarbituric acid value in the buffalo meat were 73.04, 20-98, 2.81and 1.51%, 5.46, 0.09%, 105.22 mg 100gram-1 meat, 0.80 meq O2 kg-1 and 0.28 mg malonaldehyde kg-1 respectively. The total count of bacteria, the psychrophilic bacteria were for each, coliform bacteria count, the Staphylococci aurus count, lactic acid bacteria count and yeasts and molds count of pastrama mixture were recorded 57×104, 65×102, 68×102, 14×102, 56×102 and 37×102 CFU g-1 respectively. The moisture, protein, fat , and ash % were 61.50, 15.11, 20.93 and 1.66% respectively, pH, free fatty acid ratio, cholesterol concentration, non- protein nitrogen, peroxide value and Thiobarbituric acid value were 5.54, 0.12%, 135.60 mg 100g-1 meat, 1.91%, 0.62 meq O2 kg-1 and 0.66 mg malonaldehyde kg-1 respectively.